Implementasi Sistem Manajemen Mutu dalam Proses Pembelajaran di Politeknik Pelayaran Sumatera Barat : Perspektif Mahasiswa - Wicaksono, Wahyu Galang (Jurnal Cakrawala Bahari, 2024)
To produce excellent human resources, the quality of learning in vocational education is very important. This study examines how students perceive the implementation of Quality Management System (QMS) in learning at the West Sumatra Sailing Polytechnic. The findings show that there is a positive correlation between the improvement of academic service quality and the implementation of quality management principles such as focus on process, strong leadership, human resource development, and continuous improvement. In addition, the implementation of ISO 9001 standards, organisational culture, and leadership participation enhanced the institution's credibility. Nonetheless, issues such as lack of resources, fear of change, and internal bureaucracy continue to hinder the implementation of QMS. The important role of students as the primary users of educational services is demonstrated by the need for effective participation processes. According to this study, cultural quality improvement, continuous training for employees, and the use of digital technology to support learning quality management (QMS) can improve organisational efficiency and enhance academic achievement in the era of educational globalisation